PRIORITY ASPECTS OF TEACHING FOREIGN LANGUAGES ON THE BASIS OF MODERN METHODS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper explores the priority aspects of foreign language teaching in the context of modern pedagogical methods. It examines the shift from traditional, grammar-focused instruction to approaches that emphasize communicative competence, learner-centeredness, and authentic language use. Key areas discussed include the integration of technology, the use of task-based and project-based learning, the development of intercultural competence, and the importance of assessment for learning. The paper argues that by prioritizing these aspects, educators can create more effective and engaging learning experiences that equip students with the skills necessary to communicate confidently and competently in a globalized world.